Follow-up study of graduate students from Business Computing at the Atlantic Campus of the University of Costa Rica (Revista Electrónica Calidad en la Educación Superior, 2025)
This paper presents the results of a study that investigated the characteristics of graduates from the Bachelor's program in Business Computing at the Turrialba Campus, Atlantic Campus, University of Costa Rica. Its objective was to examine the current situation of this population in relation to various aspects. A quantitative approach was used, with a sample of 67 graduates from the period 2018 to 2022. The main findings provide information on the university's impact on the formation of these professionals, as well as inputs for continuously improving the preparation of graduates. Finally, some challenges to consider when conducting this type of follow-up are highlighted, as well as the opportunity for further research.
Keywords: graduates; universities; monitoring; employment; computer science